Exploring The Impact Of Islamic Business Ethics And Relationship Marketing Orientation On Business Performance: The Islamic Banking Experience - Widana, Gusti Oka; Wiryono, Sudarso Kaderi; Purwanegara, Mustika Sufiati; Mohamad Toha, Mohamad Toha (Asian Academy of Management (AAM), 2015)
Relationship marketing emphasises the importance of building and maintaining longterm relationships with customers. Relationship marketing is strategic for banking institutions to have a better position in the market and to secure continuous banking relationships. Relationship marketing has inherently strong ethical roots. There is a positive relationship between ethics and relationship marketing because ethical principles constitute a precondition for creating the climate of collaboration necessary for successful relationship marketing. Islamic banking is created under Islamic law and is frequently considered ethical banking. To succeed in competition with conventional banks, Islamic banks must offer unique services and products differentiated by the implementation of Islamic business ethics. There is an opportunity for future empirical research to understand the relationship of Islamic business ethics to relationship marketing in creating the superior performance of Islamic banking. This study offers a conceptual model for this empirical research.